2013
DOI: 10.1590/1516-3180.2013.1316369
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile, common thrombophilia markers and risk factors in 85 young Indian patients with arterial thrombosis

Abstract: CONTEXT AND OBJECTIVE: Arterial thrombosis may occur consequent to hereditary thrombophilia and increased lipoprotein(a) [Lp(a)] and fibrinogen. Our aim was to study the prevalence of common thrombophilia markers in 85 consecutive cases of arterial thrombosis. DESIGN AND SETTING: A retrospective study was conducted from 85 consecutive young patients treated as outpatients or admitted due to stroke or myocardial infarction at a tertiary care hospital. METHODS: Eighty-five Indian patients (age < 45 years) pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
1
4
0
3
Order By: Relevance
“…5 Factor V resistance was found in only few patients (5/46 positive cases) which is in agreement with the study of wolf et al 6 However, some recent studies have reported a relatively higher frequency of APC-R in Indian population. [7][8][9] In a study by Khare et al, the prevalence of factor V Leiden was significantly higher in MI cases.…”
Section: Discussionsupporting
confidence: 89%
“…5 Factor V resistance was found in only few patients (5/46 positive cases) which is in agreement with the study of wolf et al 6 However, some recent studies have reported a relatively higher frequency of APC-R in Indian population. [7][8][9] In a study by Khare et al, the prevalence of factor V Leiden was significantly higher in MI cases.…”
Section: Discussionsupporting
confidence: 89%
“…In a case-control study conducted by Kopyta et al, the middle level of Lp(a) in stroke children was significantly higher than in controls (160 mg/dL vs. 24 mg/dL) [53]. Studies conducted on adult populations showed a weak association between a high Lp(a) level and an AIS occurrence [54][55][56][57][58]. Study of Rigal et al showed a stronger Lp(a)-AIS association in white men and blacks than in white women [59].…”
Section: Introductionmentioning
confidence: 99%
“…Researches carried out on different children populations showed no relation between PS deficiency and AIS occurrence [15,51,52,66,76]. Investigations conducted on adult populations [54,77,78] exposed a mild association between PS deficiency and arterial ischemic strokes, but due to small number of articles on this topic any accurate conclusions cannot be drawn. Frequencies of PS deficiency in pediatric and adult stroke patients based on the published data are shown in Table 6.…”
Section: Introductionmentioning
confidence: 99%
“…Etiyolojik neden saptanamayan %30-40 oranındaki bir grup ise kriptojenik inme grubunu oluşturmaktadır (4). Protein C ve S eksikliği, aktive protein C (APC) rezistansı ve trombofilik mutasyonlar iskemik inmenin etiyolojisinde yer aldığı bilinmektedir (1,5). Trombofili mutasyonları arasında en sık görülenler Faktör V (FV) Leiden G1691A ve protrombin G20210A mutasyonlarıdır.…”
unclassified
“…Trombofili mutasyonları arasında en sık görülenler Faktör V (FV) Leiden G1691A ve protrombin G20210A mutasyonlarıdır. Bu mutasyonlar ve artmış homosistein seviyeleri iskemik inme için herediter risk faktörlerini oluşturmaktadır (5). Geniş popülasyon çalışmalarında normal faktör V olgularına göre heterozigot FV Leiden G1691A mutasyonu olan olgular için 5-10 kat, homozigot FV Leiden G1691A mutasyonu olan olgular için 50-100 kat artmış venöz tromboz riski olduğu bildirilmiştir.…”
unclassified